2023
DOI: 10.3390/nu15030495
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Copper Concentrations during a Sports Season in Soccer Players

Abstract: Physical training produces changes in the concentrations of trace mineral elements. Sex differences in copper (Cu) concentrations in athletes are scarce. The objectives of this study were (i) to analyze changes in intracellular (erythrocytes and platelets) and extracellular (plasma and urine) Cu concentrations during a sports season in soccer players and (ii) to analyze sex differences. A total of 46 soccer players (22 men and 24 women) participated in the study. Three assessments were performed throughout the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 70 publications
0
0
0
Order By: Relevance
“…This section is similar to that reported by Toro-Román et al [19,21]. To ascertain Al intake, participants completed a nutritional questionnaire.…”
Section: Nutritional Anthropometric and Cardiorespiratory Assessmentmentioning
confidence: 72%
See 1 more Smart Citation
“…This section is similar to that reported by Toro-Román et al [19,21]. To ascertain Al intake, participants completed a nutritional questionnaire.…”
Section: Nutritional Anthropometric and Cardiorespiratory Assessmentmentioning
confidence: 72%
“…The present study was accepted and approved by the bioethics committee of the University of Extremadura (135/2020). The protocol was similar to that reported by Toro-Román et al [21,22]. A longitudinal study of approximately 11 months duration was carried out.…”
Section: Methodsmentioning
confidence: 86%
“…The study design was similar to that reported by Toro-Román et al [26]. The duration of the study was eleven months, and three assessments were performed: assessment 1 (first week of training (August)), assessment 2 (mid-season, end of the first regular round (January)) and assessment 3 (last week of training (May-June)).…”
Section: Methodsmentioning
confidence: 99%
“…Days before the start of the study, the participants completed a questionnaire to report on the characteristics of their menstrual cycle [26]. The questionnaire included general menstrual cycle questions (cycle length, duration of bleeding, age of onset, regularity, and pain).…”
Section: Participantsmentioning
confidence: 99%
“…The methods used to extract Mn and Mo from various blood components followed established protocols similar to those employed in other research studies (21,30,31). The method was developed entirely by the research support service of the University of Extremadura using inductively coupled plasma mass spectrometry (ICP-MS) (7900; Agilent Tech., Santa Clara, CA, USA).…”
Section: Mn and Mo Determinationmentioning
confidence: 99%